Peran Psikologi Pendidikan Dalam Manajemen Kesiswaan - Susanti Arian Fitry (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This research aims to determine the role of educational psychology in student management. This research is qualitative research with data collection methods carried out by interviews, observation and documentation. Qualitative data is analyzed through identifying data, classifying data, analyzing data, and concluding data. The results of this research show that student management organizes students to improve non-academic achievements starting from student planning, student acceptance, student organizing, student orientation, student attendance, student coaching and services, student organizations, student assessment, transfers and student alumni. Student management efforts to improve students' non-academic achievements include planning students' non-academic achievements, grouping students according to their chosen talents and interests, and developing non-academic achievements well. Supporting factors for student management in improving achievement are divided into two, namely encouragement from within (attitude towards learning, motivation to learn, concentration, retention of learning outcomes, self-confidence, intelligence, habits and ideals of students) and encouragement from outside (parents). , teachers or coaches, facilities and infrastructure, social environment), while the inhibiting factors are facilities and infrastructure and students. Therefore, educational psychology has a very important role in educational management. Educational psychology helps educational managers to understand how students learn and develop effective learning strategies. This includes understanding students' cognitive, emotional, and social development as well as how best to deliver learning material.